Enhancing Visual Abilities in Solving Mathematics Problems - Mohamad Rif’at (Faculty of Engineering, Universitas Lampung Jl. Soemantri Brojonegoro No.1 Bandar Lampung, Indonesia 35141, 2020)
This research is an experiment of categorizing visual abilities by representations of a solving problem through class experiment. The research is to investigate, explore, and enhance geometry thinking in solving mathematics problems presented visually. The tasks are cognitive strategies that rely on the visual representations and the genesis of the abilities with the assumption that the performance requires the manipulation of the visual representations. The model of the research developed from the students’ imagination of a visual problem or situations for accomplishing the solution and called binocular rivalry. The data are of interconnection for promoting visual abilities or senses, as the flexibility of thinking and the likelihood of having representations available in prior knowledge. The data analyzed by categorizing according to the visual abilities and by Control Chart of Attributes. The results are: 80% of the visual abilities are nonconforming index; the variation of visual representations is high in nonconforming index, but the depth struggle by the subjects and 70% select the general geometric figures that recognized. The conclusions are comprehensive, and the visual representations are nonconforming index, and the visual senses enhance in all categories. Keywords: Visual representation; Visual ability; Categorize visual skills; Geometry thinking; Cognitive strategy.